9p+6=3(p+8)

Simple and best practice solution for 9p+6=3(p+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9p+6=3(p+8) equation:


Simplifying
9p + 6 = 3(p + 8)

Reorder the terms:
6 + 9p = 3(p + 8)

Reorder the terms:
6 + 9p = 3(8 + p)
6 + 9p = (8 * 3 + p * 3)
6 + 9p = (24 + 3p)

Solving
6 + 9p = 24 + 3p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-3p' to each side of the equation.
6 + 9p + -3p = 24 + 3p + -3p

Combine like terms: 9p + -3p = 6p
6 + 6p = 24 + 3p + -3p

Combine like terms: 3p + -3p = 0
6 + 6p = 24 + 0
6 + 6p = 24

Add '-6' to each side of the equation.
6 + -6 + 6p = 24 + -6

Combine like terms: 6 + -6 = 0
0 + 6p = 24 + -6
6p = 24 + -6

Combine like terms: 24 + -6 = 18
6p = 18

Divide each side by '6'.
p = 3

Simplifying
p = 3

See similar equations:

| 4b=6b+-19 | | 4(x+2)=3x+11 | | 3x^2+10+8=0 | | 3p^2-28=27p | | 4(n-1)=n+14 | | 4y^3-3=-12y^2+y | | 10+2z=20 | | -6+x=-10 | | 12t-1=14t-5 | | 8k+10=13k-5 | | 3v^2-7v-20= | | 3a=5a-18 | | 6(x+2)=3(x-5) | | 5x+37=14x-62 | | x^2+5x+18=9 | | 4x+7=x+16 | | 15r+22=97 | | 3(x-4)+5(x+3)=2(3x-5)-6 | | 6(2x-5)=42 | | -4x+2(4-3x)=8-10x | | 9x-21=3+3 | | 3r+12=r+34 | | 4p+8=10p+2 | | -x^2+50x-350=0 | | 8t^2-6t=9 | | x^5-x^4+9x^3-9x^2=0 | | 2x+3=24 | | 5x^2+36x+36=0 | | 6(x-8)-(2x-2)=5x-1 | | .5(20z+18)-8=9(z-3) | | 7x+19y=-3 | | -4c+1=-7 |

Equations solver categories